Ef fect of Nitrogen Forms in the Vegetative Development of Three Pitahaya Species - Sierra-Balbuena, Angélica; Fernandez-Pavia, Yolanda Leticia; Sandoval-Villa, Manuel; Muratalla-Lua, Alfonso; García-Cué, José Luis (REVISTA TERRA LATINOAMERICANA, 2025)
Pitaya cultivation has gained global popularity due to its high profitability, exotic appearance, and nutritional properties. However, limited information exists on nutrient management and nitrogen forms that promote vegetative growth. The objective of the present research is to evaluate the ef fect of nitrogen (nitrate, ammonium, and combined) form in the nutrient solution on the vegetative development and nutritional status of three pitahaya species (Selenicereus undatus, Selenicereus sp., and Selenicereus ocamponis). The study was conducted in a greenhouse in Santa Cruz Tacache de Mina, Oaxaca, Mexico. A completely randomized design was proposed with three pitahaya species, five NH4+/NO3- ratios, and four replicates per treatment. Growth characteristics and nutrimental content in plant stems were evaluated by using analysis of variance, Tukey’s honest significant dif ference mean separation test, and factorial analyses by species and NH4+/NO3- ratio. Non-parametric Kruskal-Wallis tests were also considered when necessary. The results highlighted that in Selenicereus sp., rib diameter of the cutting and shoot increased with the 0/100 ratio; plant height, number of shoots, fresh and dry aerial matter, and root length were promoted with the 100/0 ratio. Nutritional concentration was favored in Selenicereus undatus with the 50/50 ratio, Selenicereus sp. with 100/0 ratio, and Selenicereus ocamponis with 75/25 ratio. Selenicereus sp. developed favorably in the greenhouse with ammonium nitrogen form. In conclusion, nitrogen form combinations increase, in general, three pitahaya species vegetative development.